Effect of Working After Retirement on the Mental Health of Older People: Evidence From China - Xie, Lin; Yao, Yi-dan; Tang, Li-li; Zhang, Shuo; Yang, Hua-lei; Zhang, Si-qing; Wu, Yuan-yang; Li, Zhi-yun (Frontiers in Psychiatry, 2021)
There is little empirical research on the effect of re-employment after retirement on the mental health of the elderly in China. To fill this gap in the literature, this study examines the effects of working after retirement on the psychological well-being of the elderly using data from the China Family Panel Studies. We employ the methods of ordinary least squares, ordered logit, and propensity score matching–difference in differences. The results show that working after retirement causes the mental health of the elderly to deteriorate significantly; their depression score is 0.382 higher than that of the retired who do not work. The deterioration effect of re-employment mainly impacts those aged over 60 years, women, and those with lower education background, urban household registration, higher pension, and higher social status. Working after retirement is negatively related to mental health through the mediating effects of deteriorating interpersonal relationships and lower positive attitude. It is necessary to consider psychological well-being effects and their population differences to evaluate the impact and improve the quality of policies, such as increasing retirement age and active aging.